Review of Islamic Law and the Criminal Code Against the Practice of Adultery - Wahyuziaulhaq; Kahar Muzakir (International Journal of Scientific Multidisciplinary Research, 2023)
Punishment has also been determined This article aims to describe the review of Islamic law and the criminal law code against the practice of adultery. A very bad act not only from an Islamic point of view but also from the point of view of the Criminal Code. However, by using the method of comparative analysis found differences between Islamic Law and the Criminal Code in defining the term adultery and its legal consequences. Sexual relations between young couples are not categorized as adultery in the Criminal Code because they are not currently in a legal marriage bond. The Criminal Code also does not ensnare adulterers who do not comply with Article 27 BW even though they are in a legal marriage bond. In addition, if the husband or wife of the adulterer gives permission to his partner to commit adultery, then Article 284 cannot prosecute him. Meanwhile, in the view of Islamic law, every sexual relationship outside of legal marriage ties is categorized as an act of adultery, and the in the Koran